THE EFFECT OF IRRADIATION ON ENAMEL MICRO-STRUCTURE CHANGES - Harun Gunawan; Sri Angky Soekanto; Safrida Hoesin (Journal of Dentistry Indonesia, 2015)
Radiotherapy plays an important role in the management of head and neck carcinoma therapy. The radiation dose ranges from 40 – 70 Gy, depends on the severity and location of the malignancy. Many patients experience an increased dental caries or sensitivity occurrence following radiotherapy. The objective of this study is to analyze the enamel micro-structure changes after irradiation. Nine polished enamel slabs were prepared from impacted 3rd molars. The slabs were flushed in non-ionic distilled water and dried by using air spray and divided into 3 groups, the control, 20 Gy and 40 Gy irradiation group. Irradiations were performed from Co60 using Gammacell-220E, with duration variables to produce the irradiation doses of 20 and 40 Gy. Philips pW370-XRD was used to examine specimen microstructure changes after irradiation. 1-way ANOVA was used for statistics analysis. It was revealed that grain size after 40 Gy irradiation was 66.29±2.7 nm, and after 20 Gy was 51.64±15.8 whilst 43.95±11.1 nm for the control group. The micro-stain deviation of the 40 Gy group was 0.594±0.15 N/m, and 0.45±2.6 N/m for the 20 Gy group, and 0.378±0.27 N/m for control group. Statistic analysis showed significant grain size differences between 40 Gy compared to both 20 Gy and control groups, but not between 20 Gy compared to the control group. Similarly, there were micro-stain differences between 40 Gy compared to 20 Gy and control groups, but not between 20 Gy compared to control group. It was concluded that irradiation with 40 Gy caused elevation of the enamel microstrain and apaite grainsize. Elevation of the enamel microstrain could lead to enamel crack and gave hypersensitive sensation.